Left lateral parietal rTMS improves cognition and modulates resting brain connectivity in patients with Alzheimer?s disease: Possible role of BDNF and oxidative stress - (:unkn) unknown (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2021)
Repetitive Transcranial Magnetic Stimulation (rTMS) is a non-invasive neuromodulation technique which is increasingly used for cognitive impairment in Alzheimer?s Disease (AD). Although rTMS has been shown to modify Brain-Derived Neurotrophic Factor (BDNF) and oxidative stress levels in many neurological and psychiatric diseases, there is still no study evaluating the relationship between memory performance, BDNF, oxidative stress, and resting brain connectivity following rTMS in Alzheimer?s patients. Furthermore, there are increasing clinical data showing that the stimulation of strategic brain regions may lead to more robust improvements in memory functions compared to conventional rTMS. In this study, we aimed to evaluate the possible disease-modifying effects of rTMS on the lateral parietal cortex in AD patients who have the highest connectivity with the hippocampus. To fill the mentioned research gaps, we have evaluated the relationships between resting-state Functional Magnetic Resonance Imaging (fMRI), cognitive scores, blood BDNF levels, and total oxidative/antioxidant status to explain the therapeutic and potential disease-modifying effects of rTMS which has been applied at 20 Hz frequencies for two weeks. Our results showed significantly increased visual recognition memory functions and clock drawing test scores which were associated with elevated peripheral BDNF levels, and decreased oxidant status after two weeks of left lateral parietal TMS stimulation. Clinically our findings suggest that the left parietal region targeted rTMS application leads to significant improvement in familiarity-based cognition associated with the network connections between the left parietal region and the hippocampus.
Keywords: rTMS; BDNF; Implicit memory; Oxidant status; fMRI; TRANSCRANIAL MAGNETIC STIMULATION; NEUROTROPHIC FACTOR; FUNCTIONAL CONNECTIVITY; EPISODIC MEMORY; SYNAPTIC PLASTICITY; IMPLICIT MEMORY; HIPPOCAMPAL; IMPAIRMENT; CORTEX; RECOLLECTION